1999
DOI: 10.1007/s002469900405
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Testing of the Child with Obesity

Abstract: As the prevalence of childhood obesity increases, exercise testing of obese children is likely to increase as well. This article discusses the implications of pediatric obesity for exercise testing and provides some recommendations for conducting tests and evaluating results. Studies comparing obese and nonobese children during exercise testing indicate that obese children are capable of meeting the challenges of exercise testing to nearly the same extent as their nonobese peers. Their physiologic responses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…When the aspect of carrying excessive body mass during exercise is eliminated by using a cycle ergometer in the test, absolute oxygen uptake values can differ for exercise on a treadmill and a cycle ergometer. For exercise on a treadmill, absolute VO 2 values for obese children are higher than for normal weight children [12,17] -similar results were noted in this study. In the exercises on a cycle ergometer, though, absolute oxygen uptake values in obese and normal weight children are usually at the same level [12].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When the aspect of carrying excessive body mass during exercise is eliminated by using a cycle ergometer in the test, absolute oxygen uptake values can differ for exercise on a treadmill and a cycle ergometer. For exercise on a treadmill, absolute VO 2 values for obese children are higher than for normal weight children [12,17] -similar results were noted in this study. In the exercises on a cycle ergometer, though, absolute oxygen uptake values in obese and normal weight children are usually at the same level [12].…”
Section: Discussionsupporting
confidence: 89%
“…The relative to body mass VO 2 values are seen to be to be significantly lower in obese children in exercises done both on a treadmill and a cycle ergometer [12,17]. Scaling VO 2 to fat-free mass may or may not eliminate the significant differences between obese and non-obese children [17]. Our study confirmed that significantly higher absolute and relative to fat-free mass and significantly lower relative to body mass oxygen uptake during treadmill exercise is noted in overweight boys compared to normal weight boys.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20,24 This procedure, however, underestimates the fitness of overweight and obese subjects. 25 Moreover, VO 2peak /kg body mass also underestimates the VO 2peak of taller subjects. 26 Therefore, several other fractional-power relationships have been suggested such as per kg 0.66, kg 0.75 or kg 0.87.…”
Section: Maximal Oxygen Uptakementioning
confidence: 99%
“…1 This depicts the spectrum of insulin sensitivity/resistance and the role that fitness and visceral body fat play upon insulin and health and time allotted to physical education classes has decreased [57,58]. For children, supplementary exercise and healthy nutritional changes can be successfully promoted in varying environments [59][60][61][62][63]. The most successful programs incorporate consistent dietary guidelines, reduced television viewing time, and increased physical activity into children's daily routine, including the school environment [64] (e.g.…”
Section: School-based Programs Can Improve Fitnessmentioning
confidence: 98%